Analyzing the Effect of Integrated Marketing Communication Practices on Organizational Performance - A Case Study of Allianz Insurance - Ani, Wynita Akuffo (UniMAC - GIJ, 2020)
Integrated Marketing Communication (IMC) activities, commencing almost at the onset of industrialization, is a major factor to organizations dealing with many clients for advertising their products and services. The IMC activities are entered not only as legal obligations of a firm but as a marketing and strong public relations strategy. The enhanced activities of IMC provided by companies in Ghana in the insurance sector. This project examined the effects of IMC on the performance of an organization; a case study of Allianz Insurance (GH) Limited. The reviewed literature revealed the usefulness of the IMC methodical synchronization of all sales programs predominantly: broadcasting, advertisement, sales promotion, personal selling, public relation and other forms types of communication. The various empirical review also revealed the effects of IMC tools to the performance of various organizations. Based on the literature review conducted; there are key questions that still need to be addressed, which the researcher hopes it will be addressed in the current research; the question then is what should be an ideal structure of the IMC model and how can such structure affect performance in the insurance sector? Thus, IMC could be a hindrance to customer satisfaction unless it fits the overall marketing strategy to improve performance.
THESIS